Linguistic problems caused by anatomical alterations of the hard palate of speakers with Down syndrome - Ferraz, Andreia de Melo Costa; Ghirello-Pires, Carla Salati Almeida (International Journal of Advanced Engineering Research and Science, 2022)
This study deals with dimensional changes in the hard palate of individuals with Down syndrome; which can cause impairments in the movement of articulators and make it difficult to program the speech sounds that are produced with alterations. Objective: to characterize the production of consonant sounds in Brazilian Portuguese (BP) in a group of young adults with Down syndrome, by correlating changes to the dimensions of the hard palate. Our hypothesis is that this occurs, the greater the speech alterations, the smaller the palatal width and length and the greater the height of the palate. Methodology: data collection was performed using the Speech Assessment Instrument for Acoustic Analysis with transcriptions made by three speech-language pathologists and palatal dimensions were obtained by measuring the participants' plaster models. The correlation coefficient with significance (p<0.05%) was used. Results: the most prevalent alterations were substitutions and distortions, and the phone [s] was the most altered. The substitution presented a statistically significant correlation with the palatal dimension, according to the hypothesis of the study. Changes in phones [d], [z], and [l]-coda and in syllabic structuring [bl] also had a statistically significant association with palatal dimensions. Conclusion: There were some correlations between speech alterations and the dimensions of anterior width and length of the hard palate, as proposed in the hypothesis, and thus, the hard palate may be a factor that contributes to the alterations in the consonant production of the group of people with Down syndrome studied.